Pre-exposure prophylaxis for the prevention of HIV infection in high risk populations: a meta-analysis of randomized controlled trials. - Junjun Jiang (Public Library of Science (PLoS), 2014)
Background Nearly ten randomized controlled trials (RCTs) of pre-exposure prophylaxis (PrEP) have been completed or are ongoing worldwide to evaluate the effectiveness of PrEP in HIV transmission among HIV-uninfected high risk populations. The purpose of this study was to evaluate the role of PrEP to prevent HIV transmission through a Mata-analysis. Methods A comprehensive computerized literature search was carried out in PubMed, EMbase, Ovid, Web of Science, Science Direct, Wan Fang, CNKI and related websites to collect relevant articles (from their establishment date to August 30, 2013). The search terms were "pre-exposure prophylaxis", "high risk population", "HIV infection", "reduction", "relative risk" and "efficacy". We included any RCT assessing PrEP for the prevention of HIV infection in high risk populations. Interventions of the studies were continuously daily or intermittent doses of single or compound antiretrovirals (ARVs) before HIV exposure or during HIV exposure. A meta-analysis was conducted using Stata 10.0. A random-effects method was used to calculate the pooled relative risk (RR) and 95% confidence intervals (CI) for all studies included. Results Seven RCTs involving 14,804 individuals in high risk populations were eligible for this study. The number of subjects in the experimental groups was 8,195, with HIV infection rate of 2.03%. The number of subjects in the control groups was 6,609, with HIV infection rate of 4.07%. The pooled RR was 0.53 (95% CI = 0.40 ∼ 0.71, P<0.001). The re-analyzed pooled RR were 0.61 (95% CI = 0.48 ∼ 0.77, P<0.001), 0.49 (95% CI = 0.38 ∼ 0.63, P<0.001), respectively, by excluding the largest study or two studies without statistical significance. Publication bias analysis revealed a symmetry funnel plot. The fail-safe number was 1,022. Conclusion These results show that PrEP is an effective strategy for reducing new HIV infections in high risk populations.